Public performances : studies in the carnivalesque and ritualesque - Santino, Jack (Ritual, festival, and celebration, 2017)
"A deep and wide-ranging exploration of relationships among public performance genres and the underlying political motivations they share. Illustrating the connections among three themes--the political, carnivalesque, and ritualesque--this volume provides rich and comprehensive insight into public performance as an act of power assertion"--Provided by publisher